The features for formation of favorable socio-psychological climate in the labor collective (Economics and region, 2020)
The article examines the basis for the formation of a favorable socio-psychological climate in the labor collective. The characteristics of the favorable and unfavorable socio-psychological climate of the labor collective are considered. The main factors influencing the state of the socio-psychological climate in the labor collective are determined. It is proved that the characteristic features of a team in which an unfavorable socio-psychological climate is high staff turnover and low labor efficiency. The study revealed that the leading role in the formation of socio-psychological climate in labor collective by the management, which first and foremost must understand the psychology of people, their emotional state, mood, feelings, to find an individual approach to each employee, properly to distinguish between the duties and rights of the employee and to minimize the conflict situations in the team.
Keywords: socio-psychological climate; team; satisfaction; comfort; results; cohesion; stimulation; working conditions